Treatment Outcomes for Malignant Peripheral Lung Tumours: A Prospective Single-Centre Comparison of Thermal Ablation, Surgery, and Radiotherapy - Mačionis, Aurimas; Maziliauskienė, Gertrūda; Dubeikaitė, Rūta; Balčiūnaitė, Ieva; Galnaitienė, Grytė; Padervinskienė, Lina; Matulionė, Jurgita; Miliauskas, Skaidrius; Korobeinikova, Erika; Jaruševičius, Laimonas; Nedzelskienė, Irena; Mišeikytė-Kaubrienė, Edita; et al. (Medicina (Kaunas, Lithuania), 2025)
Background and Objectives: Lung cancer and pulmonary metastases are major causes of cancer-related mortality. Surgery is a standard curative approach, but many patients are ineligible due to age, comorbidities, or treatment preference. This study aimed to evaluate the safety, effectiveness, and quality-of-life outcomes of thermal ablation versus surgery and stereotactic body radiotherapy (SBRT) for malignant lung lesions. Materials and Methods: A prospective, non-randomized study was conducted on 68 patients with primary or metastatic lung tumours treated by surgery (n = 19), SBRT (n = 29), or thermal ablation (n = 20). The key outcomes included recurrence rates and patterns, disease-free and overall survival, complications, hospitalization, and health-related quality of life (HRQoL). Results: Surgery demonstrated the lowest total and regional recurrence rates (21.1% and 10.5%, respectively), significantly lower than SBRT (57.1% and 42.9%, respectively; p < 0.05). Additionally, surgery led to the longest disease-free survival but was associated with the highest complication rate (78.9%) and the greatest HRQoL decline. SBRT had fewer complications (17.2%) and moderate HRQoL outcomes. Thermal ablation showed no significant differences in recurrence (45.0% of total recurrence) or survival compared to surgery or SBRT, with a moderate complication rate (45.0%) and the most favorable HRQoL outcomes. Major complications were rare and comparable across all groups. Conclusions: Thermal ablation demonstrated comparable disease control and quality-of-life outcomes to SBRT, with lower complication rates. While surgery remains superior in local disease control, its invasiveness and impact on quality of life underscore the importance of minimally invasive treatments in multidisciplinary management of malignant lung lesions.